1997
DOI: 10.1002/j.2048-7940.1997.tb02081.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Nursing Judgment Related to Reducing the Incidence of Falls by Elderly Patients

Abstract: The incidence of falls among elderly patients has been and continues to be a major challenge for nurses. Falls add physical injury and mental stress to patients' existing health problems, are a deterrent to rehabilitation, and increase healthcare costs. This study describes the variables that nurses identify as influencing their clinical decision making and the nursing behaviors associated with preventing patient falls. The study was grounded in the theory that discretionary nursing behaviors are related to nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 31 publications
1
24
0
4
Order By: Relevance
“…There is substantial evidence that they do. As noted by Turkoski et al. (1997), nurses expressed self‐doubt and blame following a patient fall that was sufficient to drive them from the profession.…”
Section: The 2001 Practice Review Of the Falls Prevention Programmementioning
confidence: 99%
“…There is substantial evidence that they do. As noted by Turkoski et al. (1997), nurses expressed self‐doubt and blame following a patient fall that was sufficient to drive them from the profession.…”
Section: The 2001 Practice Review Of the Falls Prevention Programmementioning
confidence: 99%
“…suggest that nurses’ clinical judgements about patients’ fall risk may aid the development of fall prevention protocols. Further research is warranted to build on limited knowledge in this area 16 …”
Section: Background and Review Of Literaturementioning
confidence: 99%
“…2 In numerous studies of falls and injuries, researchers have noted a significant incidence of falls and injuries with side rail use, [3][4][5][6][7][8][9][10][11] and several editorials and reviews of the falls literature discourage their use. [12][13][14][15][16][17] It is well recognized by physicians and nurses working in British geriatric facilities that side rails lack any known benefit in fall prevention, 18 and their prevalence is modest, only 8.4% (56/668) in one study. 19 A study conducted in a New Zealand hospital found a decease in falls and injuries after a policy to reduce side rail use.…”
mentioning
confidence: 99%